Excitation of the Secondary Modes by the Broad Spectrum Sound in a Liquid with Relaxation Losses - PERELOMOVA, Anna (Archives of Acoustics, 2024)
Features of nonlinear phenomena and, in particular, acoustic excitation of the entropy and relaxation modes in a liquid electrolyte with a chemical reaction are examined. The total range of frequencies of an exciter is considered, and the instantaneous dynamic equations are derived which govern perturbations in the secondary modes. The instantaneous leading-order acoustic forces of the secondary modes are evaluated. Examples of harmonic and nearly harmonic acoustic exciter are considered in detail. The difference in the nonlinear acoustic phenomena in an electrolyte and gases with relaxation mechanisms are specified and discussed.